Analisis Pendapatan Usahatani Bunga Potong Krisan di Desa Pancasari Kecamatan Sukasada Kabupaten Buleleng - PUTRA P, I G ANGGA DIAN; BUDIASA, I WAYAN; RANTAU, I KETUT (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Farming Income Analysis of Chrysanthemum Cut Flowers at Pancasari Village, Sukasada District, Buleleng Regency Cut flowers are one of the agricultural commodities that can help improve the income and welfare of farmers. One of the cut flowers having high economic value is chrysanthemum. The aim of this study was to determine the total cost spent by the farmers of chrysanthemum cut flowers, total incomes of chrysanthemum cut flower farming and the farmers' net income of chrysanthemum cut flower farming. This study used 30 respondents through simple random sampling. The data analysis method used was quantitative analysis method that would be obtained by using the formula of farming net income.The results showed the average costs spent by farmers of chrysanthemum cut flowers amounted to Rp. 5,941,823.71, detailed from variable and fixed costs. Acceptance in one harvest season was Rp. 15.526.500,00-, detailed from chrysanthemum cut flower crops with an average greenhouse area of 355 m2, so in one harvest season the net income earned was Rp. 9,584,676.29. The suggestion recommended in this research is that the chrysanthemum cut flower growers in the village of Pancasari should retain chrysanthemum cut flower farming because it is very profitable looked at from the high market demand the production will definitely be sold so that farmers do not have to worry about the farming and there is a need for further research on the constraints faced by the farmers of chrysanthemum cut flowers on his farm and the opportunity cost arising due to choose a farm of several alternative farming opportunities available.
Keywords: chrysanthemum; cut flowers; greenhouse; net income; farmer group